1982
DOI: 10.1111/j.1365-2362.1982.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelets from diabetic subjects show diminished sensitivity to prostacyclin

Abstract: Prostacyclin, an unstable metabolite of arachidonic acid metabolism, has been shown to have potent platelet antiaggregatory and vasodilator activity. Available evidence suggests that arterial prostacyclin production is diminished in the diabetic state. In this study we have examined the sensitivity of platelets from diabetic subjects to the antiaggregatory effects of prostacyclin in vitro and report that platelets from some diabetic patients show diminished sensitivity to the antiaggregatory effects of prostac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 9 publications
1
28
1
4
Order By: Relevance
“…73 In addition, platelets of DM patients have diminished sensitivity to the actions of NO and prostacyclin. 43,44 Endothelial dysfunction is another characteristic feature in DM patients that may result in a prothrombotic state through an increased production of tissue factor. 74 An upregulation of platelet ADP P2Y 12 receptor signaling, which suppresses cAMP levels, and a lower responsiveness to insulin have been suggested in patients with type 2 DM, leading to increased adhesion, aggregation, and procoagulant activity.…”
Section: Other Cellular Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…73 In addition, platelets of DM patients have diminished sensitivity to the actions of NO and prostacyclin. 43,44 Endothelial dysfunction is another characteristic feature in DM patients that may result in a prothrombotic state through an increased production of tissue factor. 74 An upregulation of platelet ADP P2Y 12 receptor signaling, which suppresses cAMP levels, and a lower responsiveness to insulin have been suggested in patients with type 2 DM, leading to increased adhesion, aggregation, and procoagulant activity.…”
Section: Other Cellular Abnormalitiesmentioning
confidence: 99%
“…41,42 IRSindependent pathways are also involved in platelet hyperreactivity caused by insulin resistance such as impairment in platelet sensitivity to nitric oxide (NO) and prostacyclin. 43,44 Both mediators are released by the endothelium and retard platelet activation. Therefore, impaired response to NO and prostacyclin is associated with enhanced platelet reactivity.…”
Section: Insulin Deficiency and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…5, 6 Several mechanisms are involved in this platelet dysfunction ( Figure 1): hyperglycemia enhances platelet aggregation by inducing P-selectin expression, 7 by activating protein kinase C (a mediator of platelet activation) 8 and by glycating platelet surface proteins, with consequent decrease in membrane fluidity and amplification of platelet adhesion. 9 Moreover, insulin resistance and/or deficiency in diabetic patients have been associated with impairment in the response to antithrombotic molecules (such as prostacyclin) 10 and contribute to platelet dysfunction by insulin receptor substrate-dependent effects, causing a rise in the intracellular calcium concentration and subsequent enhanced platelet degranulation. 11 Upregulation of glycoprotein (GP) IIb/IIIa surface receptors, 12 amplification of P2Y12 signaling, 13 and overproduction of reactive oxygen species 14 also contribute to the platelet dysfunction of diabetic patients; finally, metabolic conditions frequently associated with DM (ie, obesity, dyslipidemia and systemic inflammation) may also play a role.…”
Section: Biological Bases Of Platelet Hyperreactivity In Patients Witmentioning
confidence: 99%
“…For example J there are increases in alphaadrenoceptor but diminished beta-adrenoceptor activity in cardiac, smooth muscle and neural tissue (Tomlinson et al 1992). Furthermore J Betteridge et al (1982) have demonstrated that PGIrstimulated adenylate cyclase is significantly diminished in platelets from diabetic patients. Since beta-adrenoceptors are thought to act via activation of adenylate cyclase (Jakobs et ai.…”
Section: Discussionmentioning
confidence: 99%